Literacy and literacy in early childhood education: The child's perspective (Revista Contexto & Educação, 2023)
This text deals with a research, carried out on the occasion of the conclusion of the course, whose objective is to understand the children's perspective on literacy and literacy activities carried out in Early Childhood Education. It is possible to notice, in the pre school of Early Childhood Education, that there is an expectation, from teachers, parents, educational managers, to send children to the Initial Years of Elementary School, with reading and writing skills. Therefore, literacy and literacy practices end up becoming common in the finalist classes of Early Childhood Education. Considering this, based on the Sociology of Childhood (SARMENTO, 2005, 2013, 2019), a survey was carried out with children, understanding them as competent subjects, producers of knowledge and culture. In a qualitative approach, in the production of data with the children, activities were proposed based on traditional and constructivist methods of literacy and literacy (SOARES, 2003, 2004; FERREIRO, TEBEROSKI, 1985), and conversation interviews (SARAMAGO, 2003) with the research subjects. The analysis categories were divided into two: children's perspectives on traditional activities, and children's perspectives on constructivist activities. The results of the data analysis indicated that constructivist activities, based on playfulness, such as games and games, are indicated by children and become efficient to insert them into the literate world, as they respect children's logic, value the participation of children and their different forms of expression and communication.
Keywords: Children's perspective; Literacy; Childhood Education